Gaya Pacaran Anak-Anak Sekolah Dasar Dalam Perspektif Pendidikan Agama Hindu - Mariantika, Ni Putu; Suwendra, I Wayan (Jayapangus Press, 2021)
During adolescence a person experiences puberty or the transition from childhood to adolescence. Puberty is also known as physical maturation, a rapid transition that mainly occurs in the early stages of adolescence and involves changes in the body and hormones. At this time, the opposite sex begins to be attracted. Many children today are familiar with the term dating. Dating can be defined as an effort to establish a relationship and cultivate a sense of love before entering a more serious level or marriage. Dating at elementary school age has a great risk because children are mentally unprepared or unstable and not mature enough to make decisions. Therefore, the importance of early education to avoid negative things. This research uses a type of qualitative research using a descriptive analysis approach. The results of this study indicate that the importance of religious understanding must be given to children of today's young generation, in order to create a young Hindu generation with Suputra character. Hinduism does not regulate through prohibitions but teaches about true self-awareness. Hinduism recognizes the concept of Catur Asrama and Catur Purusa Artha. Basically, Catur Purusha Artha is a philosophy of life from Catur Asrama, namely the four stages of life in this world. Therefore, the younger generation, especially elementary school children, must be given assistance and understanding so that they can make good use of their childhood (Brahmacari) to learn and pursue achievements.